2006
DOI: 10.1534/genetics.105.050658
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Close Stable Homolog Juxtaposition During Meiosis in Mutants ofSaccharomyces cerevisiae

Abstract: A unique aspect of meiosis is the segregation of homologous chromosomes at the meiosis I division. The pairing of homologous chromosomes is a critical aspect of meiotic prophase I that aids proper disjunction at anaphase I. We have used a site-specific recombination assay in Saccharomyces cerevisiae to examine allelic interaction levels during meiosis in a series of mutants defective in recombination, chromatin structure, or intracellular movement. Red1, a component of the chromosome axis, and Mnd1, a chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 117 publications
2
22
0
Order By: Relevance
“…Because Cre-mediated recombination does not involve strand-exchange intermediates that might themselves promote pairing, this assay is thought to report on pairing without influencing it (S. Burgess, personal communication). As detected by this assay, CSHJ requires DSBs, DMC1 (Peoples et al 2002), RAD51 (Lui et al 2006), and axial element proteins (Peoples et al 2002). Consistent with cytological analysis of axial associations, CSHJ can be detected in the absence of synapsis and crossovers (Peoples et al 2002), indicating that the stabilization of homolog pairing depends on the initiation of crossovers, but not on their completion.…”
Section: Interhomolog Recombination Promotes Pairingsupporting
confidence: 76%
See 2 more Smart Citations
“…Because Cre-mediated recombination does not involve strand-exchange intermediates that might themselves promote pairing, this assay is thought to report on pairing without influencing it (S. Burgess, personal communication). As detected by this assay, CSHJ requires DSBs, DMC1 (Peoples et al 2002), RAD51 (Lui et al 2006), and axial element proteins (Peoples et al 2002). Consistent with cytological analysis of axial associations, CSHJ can be detected in the absence of synapsis and crossovers (Peoples et al 2002), indicating that the stabilization of homolog pairing depends on the initiation of crossovers, but not on their completion.…”
Section: Interhomolog Recombination Promotes Pairingsupporting
confidence: 76%
“…Sgs1 is a homolog of the human Bloom Syndrome helicase (BLM), a member of the RecQ family (Ellis et al 1995, Watt et al 1996. Mutations in SGS1 produce the unusual phenotype of elevated numbers of axial associations in the absence of synapsis (Rockmill et al 2003) and increased ectopic recombination in the Cre recombinase-based CSHJ assay (Lui et al 2006). Mutation of SGS1 also results in a mitotic hyper-recombination phenotype (Gangloff et al 1994, Ira et al 2003) similar to defects observed in the cancer-prone cells from Bloom Syndrome patients (Chaganti et al 1974).…”
Section: Editing Of Homolog Pairingmentioning
confidence: 92%
See 1 more Smart Citation
“…Measurement of the CSHJ phenotype in a series of mutants has shown that entry into meiosis and meiotic recombination factors are required for achieving wild-type CSHJ (Peoples et al 2002;Lui et al 2006). Mutants with defects in recombination initiation or early stages of DSB repair have severe defects in CSHJ, while those with defects in later stages of repair have moderate defects or no defect.…”
mentioning
confidence: 99%
“…The Cre/loxP site-specific recombination system provides a quantitative genetic probe of meiotic homolog pairing in living yeast cells (Peoples et al 2002;Peoples-Holst and Burgess 2005;Lui et al 2006). In an accompanying article, we show that crossover-associated meiotic recombination increases the probability of nearby Cre-mediated loxP recombination events (''collisions'') between homologous chromatids (Mell et al 2008, this issue).…”
mentioning
confidence: 98%